Republican devotions: The changing shape of the polity in early nineteenth century Colombia (2010)
The article shows that the Republic was a pivotal reference point in the political language of early nineteenth-century Colombia. By articulating old and new meanings, the Republic allows us to discuss the possibilities of an analysis that, leaving aside the nation as a privileged concept, follows the changing shape of the political community. The article first discusses some of the problems with the analytical category of nation as the privileged way to understand the post-revolutionary period. Next, it highlights the various options available at the start of the nineteenth century to refer to the political community-fatherland, nation, republican homeland- to then emphasize the centrality of republican invocations. In the third section, it shows how the idea of the Republic was pervaded by Catholic references. The article concludes by insisting how this case suggests new ways of thinking about the shape and trajectory of political communities in early nineteenth-century Colombia.